Reliability Assessment of the Integrated Energy System Considering Gas–Thermal Inertia - Zhu, Yaopei; Sun, Weijia; Miao, Cairan; Wang, Qi; Tang, Yi; Huang, Yunkai (Frontiers in Energy Research, 2022)
The electrical-thermal coupling integrated energy system has multi-time scales characteristics, and the gas-thermal slow dynamic characteristics of IES contain rich flexibility. The state of gas-thermal system changes relatively with a time delay when the external conditions change, which can provide power support for the system in a certain time scale. Based on the gas-thermal inertia power support capability, a reliability assessment method of IES considering gas-thermal inertia is proposed. According to the research, the reliability assessment of IES based on gas-thermal inertia can reduce the size and frequency of load shedding, alleviate the system operation risk caused by heavy load, reduce the system operation cost, and improve the system long-term operation reliability and economy. The greater the importance assessment index of energy conversion equipment is, the greater the impact on system reliability is, which is the weak node that needs to be focused on and protected.